Simplifying a radical expression: ((x-1/x=1)^-1/2)/(x=1)^2  TOPIC_SOLVED

Complex numbers, rational functions, logarithms, sequences and series, matrix operations, etc.

Simplifying a radical expression: ((x-1/x=1)^-1/2)/(x=1)^2

Postby mmh28 on Wed Aug 26, 2009 4:40 pm

On p. 34 of Schaum's Outline, Calculus, Frank Ayres, problem 40 gives the derivative of of f(x)=(x-1/x=1)^1/2 as I/(x=1)(x^2-1)^1/2.

I get as far as ((x-1/x=1)^-1/2)/(x=1)^2 but cannot reduce it to the answer given. Can someone help.

Thanks
MMH
mmh28
 
Posts: 3
Joined: Wed Aug 26, 2009 4:27 pm

Sponsor

Sponsor
 

Postby stapel_eliz on Wed Aug 26, 2009 5:12 pm

mmh28 wrote:...the derivative of of f(x)=(x-1/x=1)^1/2....

For what mathematical operation is your book using the second "equals" sign above?

Also, your formatting is unclear. As written, the function is:

. . . . .

Was the above what you meant, or did you mean something more like the below?

. . . . .

Thank you! :wink:
User avatar
stapel_eliz
 
Posts: 1783
Joined: Mon Dec 08, 2008 4:22 pm

Re: Simplifying a radical expression: ((x-1/x=1)^-1/2)/(x=1)^2

Postby mmh28 on Wed Aug 26, 2009 8:58 pm

Oops! I just discovered that the plus sign on my numeric pad prints out an equal sign. Weird.

I'll try again:http: :confused:

f(x) = ((x-1)/(x+1))^1/2
f'(x) = ((x-1)/(x+1))^-1/2)/(x+1)^2 (my answer, which I think is correct but can't get it in the form given in the book).

Answer in Schaum's: f'(x) = I/(x+1)(x^2-1)^1/2

Your second example, but with x+1 in the denominator, is what I intended.
I'm new to the forum but can't find out how to format with the actual radical sign as you have.

Many thanks
MMH
mmh28
 
Posts: 3
Joined: Wed Aug 26, 2009 4:27 pm

  TOPIC_SOLVED

Postby stapel_eliz on Thu Aug 27, 2009 11:47 am

mmh28 wrote:Answer in Schaum's: f'(x) = I/(x+1)(x^2-1)^1/2

What is meant by the "pipe" character in the numerator of the above? Is the radical in the numerator (multiplied against the fraction, and thus ending up on top) or in the denominator?

Note: I get the first step in the derivative as being:

. . . . .

This simplifies as:

. . . . .

Reduce, note that (x + 1)3/2 = (x + 1)*sqrt[x + 1], and recall what is the product of (a + b)(a - b), for inside the resulting radical.... :wink:
User avatar
stapel_eliz
 
Posts: 1783
Joined: Mon Dec 08, 2008 4:22 pm

Re: Simplifying a radical expression: ((x-1/x=1)^-1/2)/(x=1)^2

Postby mmh28 on Fri Aug 28, 2009 1:39 pm

Thank you! It was driving me mad.

MMH
mmh28
 
Posts: 3
Joined: Wed Aug 26, 2009 4:27 pm


Return to Advanced Algebra ("pre-calculus")